2003
DOI: 10.1002/ajh.10391
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting long‐term survival in low‐risk diffuse large B‐cell lymphoma

Abstract: The International Prognostic Index (IPI) is widely used for risk stratification of patients with diffuse large B-cell lymphoma (DLBCL). However, even among patients with low-risk disease, according to the IPI a substantial proportion of patients ultimately succumb to their disease. Using mature population-based data from the Danish Lymphoma Group, we analyzed if prognostic clinical pretreatment factors could be identified in patients with lowrisk DLBCL. One hundred seventy-seven patients, all with a prognostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(20 reference statements)
2
3
1
Order By: Relevance
“…In the multivariate survival analysis, older age, the presence of B-symptoms, abnormal serum LDH, more advanced clinical stage (III/IV), and TIMP-1 expression were related to poorer overall survival in the patients with diffuse large B-cell lymphoma. This result is in agreement with those of previous studies of diffuse large B-cell lymphoma using tissue microarray, [59][60][61][62] reflecting the reliability and robustness of our data. Therefore, TIMP-1 expression is an independent factor, and represents a marker for poor prognosis with potential therapeutic implications.…”
Section: Discussionsupporting
confidence: 93%
“…In the multivariate survival analysis, older age, the presence of B-symptoms, abnormal serum LDH, more advanced clinical stage (III/IV), and TIMP-1 expression were related to poorer overall survival in the patients with diffuse large B-cell lymphoma. This result is in agreement with those of previous studies of diffuse large B-cell lymphoma using tissue microarray, [59][60][61][62] reflecting the reliability and robustness of our data. Therefore, TIMP-1 expression is an independent factor, and represents a marker for poor prognosis with potential therapeutic implications.…”
Section: Discussionsupporting
confidence: 93%
“…This corresponds with the results reported by Møller et al, 22 who also found that age and clinical stage influence the survival of patients with DLBCL. Ho et al 24 also report that the prognosis is influenced by clinical stage and histologic grade because large cell lymphomas are considered aggressive and have a poor prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…12,20,21 Studies such as that of Møller et al 22 reported the survival of patients with DLBCL without specifying the location of the tumor, and found an overall survival rate of 85% at 5 years, which is much higher than the value determined in this study (45% at 5 years). This may be because in cases in OC- MR, patients often take too long to seek medical attention, which results in more difficult treatment and poorer prognosis.…”
Section: Discussioncontrasting
confidence: 66%
“…Bone marrow (BM) examination is an integral part of the Ann Arbor staging system for all lymphoproliferative malignancies [1,2,5]. In non-Hodgkin lymphoma (NHL), Ann Arbor stage III to IV disease is an adverse prognostic feature in the International Prognostic Index [5][6][7][8]. BM involvement by PTLD defines stage IV disease; and similar to immunocompetent patients with NHL, patients with advanced-stage PTLD are known to have inferior prognosis and shorter overall survival [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%